PENGANGGURAN DALAM PERSPEKTIF EKONOMI ISLAM DAN KOVENSIONAL - Doni, Amsah Hendri; Alfiona, Fifa; Andespa, Wira; Al-Amin, Al-Amin (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2023)
High unemployment is an economic problem and a social problem. Unemployment is an economic problem because when the unemployment rate increases as a result a State discards goods and services that can actually be produced by unemployment. The purpose of this study is to find out how unemployment in the Islamic and conventional economic perspective. This research method is This research is a type of library research; i.e. the data and study materials that are included in the use come from literary sources, both in the form of books. The result of this study is Unemployment and poverty arise when a person or group of people is unable to meet the level of economic prosperity that is considered the minimum requirement of a certain standard of living, Islam responds to unemployment and provides solutions by increasing and bringing in halal investments to be developed in the real sector both in agriculture and forestry, marine, and mining as well as increasing trade volumes